Advances in Microbial Poly(3‐hydroxybutyrate‐co‐3‐hydroxyvalerate) over the Past 5 Years: Applications in Medicine, Food and Environment - Shi‐Heng Zhang; Jin‐Wei Dao; Dai‐Xu Wei (Journal of Polymer Science, 2026)
ABSTRACT Poly(3‐hydroxybutyrate‐co‐3‐hydroxyvalerate) (PHBV) is a prominent member of the polyhydroxyalkanoate (PHA) family and has emerged as one of the most promising biopolymers for biomedical applications owing to its exceptional biocompatibility, biodegradability, thermoplastic processability, and biological safety. This review systematically summarizes recent advances in PHBV research, encompassing intrinsic property modulation, functional modification strategies, and manufacturing technologies for medical devices. The fundamental characteristics of PHBV are first outlined, including the 3‐hydroxyvalerate molar fraction‐dependent tunability of material properties, biodegradation behaviors across diverse environmental media, and inherent thermoplastic and biosafety profiles. We also discuss filler‐based modification strategies to modulate degradation rates and their relevant mechanisms. It also assesses fabrication techniques for shaped PHBV devices. Recent achievements and quantitative data are compiled to demonstrate the expanding applications of PHBV in biomedicine (e.g., musculoskeletal regeneration, wound healing, sustained drug delivery, anticancer therapy, and electroactive biomaterials), the food industry, and environmental remediation. Existing challenges impeding the industrial translation of PHBV, including high production costs, limited processability of neat PHBV, and difficulties in precise degradation control, are identified. We also propose future research directions such as cost‐effective sustainable production routes intelligent stimulus‐responsive composite materials and high‐value cross‐domain applications.